2021
DOI: 10.1021/acs.jpcc.1c09033
|View full text |Cite
|
Sign up to set email alerts
|

Designing Highly Luminescent Molecular Aggregates via Bottom-Up Nanoscale Engineering

Abstract: Coupling of excitations between organic fluorophores in J-aggregates leads to coherent delocalization of excitons across multiple molecules, resulting in materials with high extinction coefficients, long-range exciton transport, and, in particular, short radiative lifetimes. Despite these favorable optical properties, uses of J-aggregates as high-speed light sources have been hindered by their low photoluminescence quantum yields. Here, we take a bottom-up approach to design a novel J-aggregate system with a l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…598 As an example, the left portion of Figure 31B shows the structure of a recently reported J-aggregate-forming dye, Cy3UB. 599 Like many such aggregate-forming dyes, this is a cyanine dye, the planarity and large polarizability of which favors aggregate formation in poor solvents, and even the isolated molecule shows a fairly narrow emission spectrum (Figure 31B center), with the aggregate (Figure 31B right) clearly showing the three characteristics of J-aggregate spectra noted above, notably a narrower 0,0 emission.…”
Section: Figure 26mentioning
confidence: 85%
“…598 As an example, the left portion of Figure 31B shows the structure of a recently reported J-aggregate-forming dye, Cy3UB. 599 Like many such aggregate-forming dyes, this is a cyanine dye, the planarity and large polarizability of which favors aggregate formation in poor solvents, and even the isolated molecule shows a fairly narrow emission spectrum (Figure 31B center), with the aggregate (Figure 31B right) clearly showing the three characteristics of J-aggregate spectra noted above, notably a narrower 0,0 emission.…”
Section: Figure 26mentioning
confidence: 85%
“…It was previously confirmed that the concentrations of rhodamine 6G used in 0.1 mm cuvettes do not lead to the quenching of the dye, retaining the same high QY. [ 44 ] Fluorescence spectra were collected using the front facing geometry, where rhodamine 6G and J‐aggregates were excited using 500 and 565 nm excitation sources, respectively. The QY of TDBC J‐aggregates was calculated using the ratio of the slopes of the calibration plots, taking into account differences in refractive indices and the power of excitation sources.…”
Section: Methodsmentioning
confidence: 99%
“…The methanol solution of TDBC has a relatively low QY of 3%. [42,44] This is because of the flexible trimethine chain, where excited-state C-C rotations act as a major nonradiative recombination pathway reducing the PL QY. [45,46] It has been shown that rigidification of the polymethine chain in many cyanine dyes using fused ring systems leads to a significantly improved PL QY.…”
Section: Characterization Of the Tdbc Molecule And Its Self-assembly ...mentioning
confidence: 99%
“…The increased relative intensity of the 0,0 subpeak can been explained using quantum-mechanical analysis of the vibronic structure, while the 0,0 peak is narrowed due to rapid motion of the exciton between different sites . As an example, the left portion of Figure B shows the structure of a recently reported J-aggregate-forming dye, Cy3UB . Like many such aggregate-forming dyes, this is a cyanine dye, the planarity and large polarizability of which favors aggregate formation in poor solvents, and even the isolated molecule shows a fairly narrow emission spectrum (Figure B, center), with the aggregate (Figure B, right) clearly showing the three characteristics of J-aggregate spectra noted above, notably a narrower 0,0 emission.…”
Section: Current State Of Knowledge and Technology By Materialsmentioning
confidence: 99%
“…(A) Schematic showing how a side-by-side (H-aggregate) alignment of chromophore transition dipoles leads to a low-energy nonemissive state but how end-to-end (J-aggregate) alignment leads to an emissive state lower in energy than that of the monomer. (B) Structure of Cy3UB, an example of a cyanine dye reported to form J aggregates, along with absorption and emission spectra of monomeric Cy3UB in MeOH and of Cy3UB J aggregates in 9:1 MeOH/H 2 O. Spectra reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Current State Of Knowledge and Technology By Materialsmentioning
confidence: 99%